Changing Nature of Capitalism in the Era of Globalization through YouTube: A Perspective of Consumerism - Nath, Dipika (Department of Public Administration, 2024)
The contemporary concept of globalization emerged during the 1980s under the influence of leaders like Ronald Reagan and Margaret Thatcher, who promoted privatization as a pathway to globalization. This idea gained widespread popularity in the 1990s. Postmodern scholars such as Paul-Michel Foucault, Jean Baudrillard, Arjun Appadurai, and Douglas Kellner argue that globalization is a top-down process legitimizing capitalist logic, where technology plays a pivotal role in fostering